SPECTRUM OF ZYGOMATIC COMPLEX FRACTURE AT A TERTIARY CARE CENTER OF NEPAL - Gautam, Shailesh; Kumar Shah, Arun; Chaurasia, Nitesh (Journal of Chitwan Medical College, 2024)
Background: Zygomatic bone is complex bilaterally located bone of face contributing to aesthetic and function. Zygomatic complex fracture is common type of facial bone fracture in young male with periorbital ecchymosis, flattening of cheek being common clinical presentation and Road Traffic Accident (RTA) being common etiology. Its treatment depends upon various factors like demographics, clinical findings, socioeconomics, fracture type and available resources. Present study is aimed to evaluate various clinical and other preoperative spectrums of ZMC fracture. Methods: This was a descriptive cross-sectional study conducted at Department of Oral and Maxillofacial Surgery in a tertiary center for 1 year, after taking consent in 86 patients. Convenience sampling was used after confirmation of ZMC fracture by CT scan. Data was collected, assembled, analyzed by SPSS and presented in table and graphs. Results: Mostly male 74(86%) of age group 20-39 years 42(48.8%) were involved in ZMC fracture. RTA was most common etiology accounting for 68.6%. Common presentations were subconjunctival hemorrhage, periorbital hematoma, trismus, flattening of cheek and orofacial laceration accounting for 90.1%, 84.9%, 54%, and 58.1% respectively. Nasal fracture was associated in 33.7% cases and extremity fracture in 20.9% cases. 84.9% cases were of displaced type and 48.8% were of tetrapodal fracture. Conclusions: This study in different preoperative parameters of ZMC fracture would be helpful in educating society regarding etiologies and precautions to be taken, for policy makers to make and enforce regulations to minimize incidences and for health workers to evaluate, diagnose and better multidisciplinary management.